Ecological character displacement in the face of gene flow: evidence from two species of nightingales - Reifová, Radka; Reif, Jiří; Antczak, Marcin; Nachman, Michael W (BMC evolutionary biology, 2011)
BACKGROUND: Ecological character displacement is a process of phenotypic differentiation of sympatric populations caused by interspecific competition. Such differentiation could facilitate speciation by enhancing reproductive isolation between incipient species, although empirical evidence for it at early stages of divergence when gene flow still occurs between the species is relatively scarce. Here we studied patterns of morphological variation in sympatric and allopatric populations of two hybridizing species of birds, the Common Nightingale (Luscinia megarhynchos) and the Thrush Nightingale (L. luscinia). RESULTS: We conducted principal component (PC) analysis of morphological traits and found that nightingale species converged in overall body size (PC1) and diverged in relative bill size (PC3) in sympatry. Closer analysis of morphological variation along geographical gradients revealed that the convergence in body size can be attributed largely to increasing body size with increasing latitude, a phenomenon known as Bergmann's rule. In contrast, interspecific interactions contributed significantly to the observed divergence in relative bill size, even after controlling for the effects of geographical gradients. We suggest that the divergence in bill size most likely reflects segregation of feeding niches between the species in sympatry. CONCLUSIONS: Our results suggest that interspecific competition for food resources can drive species divergence even in the face of ongoing hybridization. Such divergence may enhance reproductive isolation between the species and thus contribute to speciation.
Keywords: fenotyp; Male; životní prostředí; Phenotype; Poland; Česká republika; Environment; tok genů; biologická evoluce; mužské pohlaví; zpěvní ptáci; Czech Republic; Animals; Body Size; Biological Evolution; zvířata; velikost těla; Songbirds; Polsko; Gene Flow